2018
DOI: 10.1093/bioinformatics/bty336
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Locator, online analysis and visualization of gene clustering

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…2). We then formally analyzed the distribution of genes along the chromosomes using Cluster Locator (http://clusterlocator.bnd.edu.uy/) [44] and the D. melanogaster reference genome (Flybase Release 6.17) with a Max-gap = 5 parameter. Two-sided Kolmogorov-Smirnov tests were used to determine if the genes entered in the list were uniformly distributed along the chromosome arms and whether the numbers of realized clusters is different to 1000 randomly generated gene lists.…”
Section: Resultsmentioning
confidence: 99%
“…2). We then formally analyzed the distribution of genes along the chromosomes using Cluster Locator (http://clusterlocator.bnd.edu.uy/) [44] and the D. melanogaster reference genome (Flybase Release 6.17) with a Max-gap = 5 parameter. Two-sided Kolmogorov-Smirnov tests were used to determine if the genes entered in the list were uniformly distributed along the chromosome arms and whether the numbers of realized clusters is different to 1000 randomly generated gene lists.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, although STRING analysis of the vtRNA1-1 associated 37 protein coding genes did not find enriched process or pathways, 36 of the 37 correlated genes are located at chromosome 5q region. Using the Cluster Locator algorithm ( Pazos Obregón et al , 2018 ), we found a statistically significant non-random clustering behavior for the chromosomal location of the genes co-regulated with vtRNA1-1 (p-value < 1×10 -10 ). Indeed, when the analysis was extended to 173 protein coding genes with Spearman correlation rs ≥ 0.3, 139 genes of 173 were situated at chromosome 5q region (p-value < 1×10 -10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pathway enrichment analysis was done using STRING software for the Gene Ontology Biological Process and KEGG pathways categories ( Szklarczyk et al , 2017 ). The cluster localization analysis was performed with two approaches, the Cluster Locator algorithm ( Pazos Obregón et al , 2018 ) and the Enrichr software ( Kuleshov et al , 2016 ) ( Extended Data : Tables S9 and S10).…”
Section: Methodsmentioning
confidence: 99%
“…The pathway enrichment analysis was done using STRING software for the Gene Ontology Biological Process and KEGG pathways categories (Szklarczyk et al, 2017). The cluster localization analysis was performed with two approaches, the Cluster Locator algorithm (Pazos Obregón et al, 2018) and the Enrichr software (Kuleshov et al, 2016).…”
Section: Pathway Enrichment and Cluster Chromosome Localization Analymentioning
confidence: 99%